On-Chip Active Filter for Electrocardiographic Signals Through CMOS Pseudo Resistors - Gonzalez-Diaz, Victor R. Gonzalez (IEEE transactions on circuits and systems. II, Express briefs, 2025)
This brief describes the conception, analysis, and design of a 20.89-hertz band-pass front-end analog filter tailored for biopotential signals. The principle of operation considers the integration of active circuits exhibiting large time-constant networks by CMOS pseudo resistances. A strategic location of these pseudo resistances enables the filter to achieve the corresponding design specifications with no external capacitors. The experimental results with a CMOS 180 nanometer integrated circuit prototype achieve a competitive Figure of Merit in a 0.06 square millimeters area, exhibiting advantages in area and system performance.